Simulations and measurements of dipole and quadrupole magnets for PBP-CMU linac system - Boonpornprasert,P. (Elsevier BV, 2015)
The PBP-CMU Linac system has been established to generate femtosecond electron bunches and to study their applications, especially for generation of coherent terahertz (THz) radiations. The dipole magnet and the prototype quadrupole magnet for the system have been designed and fabricated in house. Both the simulated and the measured results were used for evaluating the magnet performance and will be used as a guideline for design and fabrication of magnet devices in the future. © 2013 The Authors.